A STRATEGI PAIKEM GURU AKIDAH AKHLAK DALAM PENINGKATAN MOTIVASI BELAJAR SISWA DI MAN 3 JOMBANG: STRATEGI PAIKEM GURU AKIDAH AKHLAK DALAM PENINGKATAN MOTIVASI BELAJAR SISWA DI MAN 3 JOMBANG - Zahroh, Fatimatuz; Inayatul Ilahiyah, Iva (PAI FAI UNHASY Tebuireng Jombang, 2025)
The PAIKEM strategy can be said to be an effort that has weight to create a creative atmosphere and learning outcomes. Because this strategy is considered to spawn many variations that are fun to learn. The purpose of the scientific study that has been compiled is to explore knowledge about aqidah teachers in motivating students, the role of aqidah moral teachers in implementing PAIKEM strategies to increase students' learning motivation, as well as the supporting and inhibiting factors. In this structured research using an appropriate method, namely qualitative and its types have been determined case studies, the techniques used are interviews as well as observations to obtain important data and documents. The researcher explained that the result is that the role of the teacher of aqidah akhlak at MAN 3 Jombang is not only teaching, but also advising, guiding, nurturing, and most importantly motivating students in madrasas so that they can realize students who have good morals. Whereas the PAIKEM strategy carried out by akhidah akhlaq teachers is by applying methods that have an effect on increasing learning motivation through active, innovative, creative, effective and fun learning. Supporting factors are adequate infrastructure, training for teachers, enthusiastic enthusiasm of students, comfortable classroom environment. While the inhibiting factor is in the condition of the students themselves including family and environment.